Seventh Congress of Rheumatologists of Russia with international participation (25–28 April 2017, Moscow) - E. L. Nasonov; V. N. Amirdzanova (Научно-практическая ревматология, 2017)
Seventh Congress of Rheumatologists of Russia with international participation (25–28 April 2017, Moscow).